APPLE GROWING IN INTENSIVE HORTICULTURE: ANALYSIS OF TECHNOLOGY AND PRACTICAL EXPERIENCE (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
This work highlights the importance of modern methods of organizing intensive apple orchards, including land selection, planting scheme, variety selection, irrigation system, and agrotechnical measures. Also, the agrotechnical work carried out in the experimental field during 2024–2026 is analyzed and their impact on yield and fruit quality is substantiated.